If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 11x + -4 = -5 Reorder the terms: -4 + 11x = -5 Solving -4 + 11x = -5 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '4' to each side of the equation. -4 + 4 + 11x = -5 + 4 Combine like terms: -4 + 4 = 0 0 + 11x = -5 + 4 11x = -5 + 4 Combine like terms: -5 + 4 = -1 11x = -1 Divide each side by '11'. x = -0.09090909091 Simplifying x = -0.09090909091
| y=-1/2x-2 | | 59=7x-11 | | 13+6x=61 | | 3*(4a-3)=-2a-2a+23 | | 8x-7=105 | | 3x(4a-3)=-2a-2a+23 | | x+2/2=7-x+1/3 | | 2x^3/2*-3^-3/2 | | 2(y-3)=20 | | 125*x^5-171*x^4+103*x^3+224*x^2-508*x+240=0 | | x+x+15+4x-22=1139 | | 2(x-7)=6x+10 | | 65-4x=14x+21 | | 10-3=(2x-1) | | 10-3=5(d-4) | | 10x+30=-5x | | 25^(-3/2) | | 4c+8=-88-8x | | Z=ax^2+3by | | 2*x^4-3*x^3+3*x^2-3*x+2=0 | | 2x+12=-13-9x | | 4x-(2x+6)=3x-26 | | x+(15+x)+(-2+4*x)=1139 | | -3(10x-12)+15x=54 | | 4.2x-6.1y+9.7=0 | | (10-x)(6+x)=64 | | 5x^2-20x-20=16x-4x^2 | | 4(x-3)-6x=-30 | | 6x-10y=70 | | 9*2+-3*4+2*9*2=3*9*2+-3*4 | | 5*(2x+10)=40 | | -12+6x=-66 |